The use of thermoresponsive nanoparticles for targeting cancer cells - MOIR, LEE A (2016)
The aim of this thesis was to investigate a dual method of targeting cancer cells with a nanoparticle system containing both a thermoresponsive corona and folate tag. The nanoparticle system used a ï¿½hide-and-revealï¿½ motif whereby the folate tag would only be revealed above the transition temperature of the thermoresponsive corona. There were difficulties encountered during the synthesis of poly(lactide-co-glycolide) (PLGA) for the further polymerisation of the thermoresponsive copolymer therefore poly(lactide) (PLA) was synthesized as an alternative. The initial thermoresponsive polymer library synthesised (PLGA-b-poly((polypropylene glycol methacrylate)-stat-(oligoethylene glycol methacrylate))) when assembled into nanoparticles had a transition temperature (Tt) of 40 ï¿½ 65 Â°C and thus did not have a low enough Tt for the cell studies. A second polymer library (PLA-b-P((diethylene glycol methacrylate)-stat-(oligoethylene glycol methacrylate)), PLA-b-P(DEGMA-stat-OEGMA)) when assembled into NPs had a Tt of between 28 ï¿½ 78 Â°C when the DEGMA:OEGMA ratio was altered from 100:0 to 50:50. In addition to the thermoresponsive polymer library, three folate tagged amphiphilic polymers were synthesised. The polymers were PLA-b-polyethylene glycol (PLA-PEG) with a terminal folate. Each of the three PLA-PEGx polymers were synthesised with a different length of PEG, PEG450, PEG3k and PEG10k. A reproducible method of nanoparticle assembly was developed which produced nanoparticles of an average radius of ?100 nm when PLA-b-P(DEGMA-stat-OEGMA) polymers were used. Three methods of controlling the overall aggregation temperature were put forward. By assembling NPs using one type of PLA-b-P(DEGMA-stat-OEGMA) the Tt of the NPs was dependent on the ratio of DEGMA:OEGMA. It was also possible to control the aggregation temperature by mixing two types of PLA-b-P(DEGMA-stat-OEGMA) polymers (provided the difference in DEGMA:OEGMA between the two polymers was between 0 ï¿½ 10 %). In addition by mixing PLA-b-P(DEGMA-stat-OEGMA) preformed NPs the aggregation temperature could be controlled similar to that for polymer blend NPs. The NPs were tested in both MCF-7 and HCT116 cell lines and were shown to have no adverse effect on the cell metabolism or membrane integrity when the NP concentration was below 4 mg/mL. It was found that there was in increase in uptake of the thermoresponsive NPs when incubation temperature was above the NPs Tt. When the PEG450 and PEG3k linked folate was used an increased uptake was observed in MCF-7 cells however no difference in uptake was observed in HCT116 cell line. Overall the ï¿½hide-and-revealï¿½ motif on this NP system was shown to be successful in enhancing the uptake in folate receptor positive cells.